How Important Are Linguistic Competencies on the German Labour Market? a Qualitative Content Analysis of Job Advertisements - Kraft, Michael Hans Gino; Hinrichs, Gerriet (European Journal of Economics and Business Studies, 2019)
Linguistic competencies (LC) are in many companies and industries an essential prerequisite for employees to accomplish tasks and integrate into a job. Under this premise, this paper summarizes the arguments and counterarguments within the scientific discussion on the relevance of LC in Job advertisements (J-Ads) in the German labour market. The main purpose of the research is to uncover the different importance of LC in the respective officially occupational category (OC) to examine whether connections between required LC and the tasks from the J-Ads. Therefore, this research represents an analysis of LC with regard to J-Ads, which was conducted on the basis of a qualitative content analysis. For the methodology of the research, 180 J-Ads were examined on the criteria of KLdB 2010. The investigation took place in a period from November 2018 to February 2019. The paper provides first evidence for the different importance of LC for the different OC and indicates ambiguities within J-Ads. Given evidence there are considerable inconsistent discrepancies between the required LC for applicants and the tasks to be performed, which can lead to inefficiencies in the recruiting process. The study confirms and proves that, in addition to implementation and conceptual problems, some management questions regarding the exploitation of LC in J-Ads can also be optimized through improved awareness and clarification of the ambiguity of the competence term.
Keywords: German labour market, Job advertisements, linguistic competencies, qualitative content analysis, occupational category